Shining a light on the photo-sensitisation of organic-inorganic hybrid polyoxometalates - Cameron, Jamie M.; Wales, Dominic J.; Newton, Graham (Royal Society of Chemistry, 2018)
Finding new ways of using visible light (or, more specifically, solar irradiation) to drive commercially significant and/or challenging chemical processes is an ongoing research goal. Polyoxometalates (POMs) are discrete, metal-oxide clusters which are cheap, robust and easily synthesized but can also act as versatile molecular building blocks, allowing for astonishing variety in their structures and properties. In particular, the rich redox chemistry and inherent photo-activity of POMs makes them attractive for use in a variety of photochemical applications however POMs characteristically only absorb strongly in the UV region. In this perspective, we discuss the various strategies which have been employed in order to sensitize POMs to visible light, with a particular focus on hybrid inorganic-organic POM species. We will discuss the two clear photo-activation mechanisms which have been developed to date and provide an outlook on some of the possible future directions of the field.